PUBLIC POLICY EVALUATION AND ENVIRONMENTAL DISASTER MITIGATION PREDICTION REGARDING THE CANCELLATION OF THE GLASS INDUSTRY STRATEGIC DEVELOPMENT IN REMPANG ISLAND - Vivin Delvya Roza; Yustina Yustina (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the evaluation of public policy and environmental disaster mitigation predictions regarding the cancellation of the strategic glass industry development in Rempang Island. The study employed a qualitative approach with a case study design and data collection through systematic literature review. Data analysis was conducted using the interactive model of Miles, Huberman & Saldana (2014). The results show that the Rempang Eco City National Strategic Project (NSP) failed comprehensively due to a procedurally flawed and non-participatory formulation process. Economic valuation research by Trend Asia et al. (2025) found that the average household income of Rempang residents reached IDR 32.77 million per household per month, far exceeding the government’s claim of IDR 3 million, while potential environmental losses reached IDR 109 million per household per month. Based on Dunn’s (2003) six policy evaluation criteria, this policy proved to be ineffective, inefficient, inadequate, inequitable, unresponsive, and inappropriate. President Prabowo Subianto’s decision to exclude Rempang Eco City from the NSP list through Presidential Regulation No. 12 of 2025 was the right step, yet still requires more decisive regulation to provide legal certainty for affected communities.